2023
DOI: 10.1002/advs.202302804
|View full text |Cite
|
Sign up to set email alerts
|

Group 3 Innate Lymphoid Cells Exacerbate Lupus Nephritis by Promoting B Cell Activation in Kidney Ectopic Lymphoid Structures

Feng Li,
Zhou Liang,
Haojie Zhong
et al.

Abstract: Group 3 innate lymphoid cells (ILC3s) represent a new population in immune regulation, yet their role in lupus nephritis (LN) remains elusive. In the present work, systemic increases in ILC3s, particularly in the kidney, are observed to correlate strongly with disease severity in both human and murine LN. Using MRL/lpr lupus mice and a nephrotoxic serum‐induced LN model, this study demonstrates that ILC3s accumulated in the kidney migrate predominantly from the intestine. Furthermore, intestinal ILC3s accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“… 38 Recent studies have also revealed the migratory capacity of intestinal ILC3s toward the kidneys. 39 Similarly, our findings also indicate that intestinal ILC3s have a strong tendency of homing to the liver. This finding implies that the increased presence of ILC3s in the liver after WMT is likely due to their migration from the intestine.…”
Section: Discussionsupporting
confidence: 77%
“… 38 Recent studies have also revealed the migratory capacity of intestinal ILC3s toward the kidneys. 39 Similarly, our findings also indicate that intestinal ILC3s have a strong tendency of homing to the liver. This finding implies that the increased presence of ILC3s in the liver after WMT is likely due to their migration from the intestine.…”
Section: Discussionsupporting
confidence: 77%